Age-associated alterations in the levels of cytotoxic lipid molecular species and oxidative stress in the murine thymus are reduced by growth hormone treatment. (October 2017) - de Mello-Coelho, Valeria; Cutler, Roy G.; Bunbury, Allyson; Tammara, Anita; Mattson, Mark P.; Taub, Dennis D.
Highlights: Basal inflammation, oxidative stress and lipotoxicity occur in the aging thymus. Lipid peroxidation increases in total thymus and thymocytes with age. Aging decreases sphingomyelin levels and increases ceramides content in thymocytes. Short treatment with GH reduces levels of free-cholesterol and 4-HNE in aged mice. GH increases dihydroceramides locally and decreases thymocyte apoptosis in aged mice. Abstract: During age-associated thymic involution, thymocytes decrease and lipid-laden cells accumulate. However, if and how aging affects the thymic lipid profile is not well understood, nor is it known if the hormonal milieu modifies this process. Here we demonstrate a correlation between reduced thymocyte numbers and markers of inflammation and oxidative stress with age. Evaluating the lipidomics profile of the whole thymus, between the ages of 4 (young) and 18 months (old), we found increased amounts of triacylglycerides, free cholesterol, cholesterol ester and 4-hydroxynonenal (4-HNE) with age. Moreover, levels of C24:0 and C24:1 sphingomyelins and ceramide C16:0 were elevated in 12–14 month-old (middle-aged) mice while the levels of sulfatide ceramide and ganglioside GD1a increased in the old thymus. Evaluating isolated thymocytes, we found increased levels of cholesterol ester and 4-HNE adducts, as compared to young mice. Next, we treated middle-aged mice with growth hormone (GH), which has been considered a potent immunomodulator. GH reduced thymic levels of TNF-α and 4-HNE and increased the number of thymocytes as well as the thymic levels of dihydroceramide, a ceramide precursor and autophagic stimuli for cell survival. In conclusion, GH treatment attenuated inflammation and age-related increases in oxidative stress and lipotoxicity in the thymus.